2008
DOI: 10.1007/978-3-540-87599-4_16
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Library Services with Web 2.0 Functionalities

Abstract: Abstract. In this paper, a prototype of an Online Public Access Catalog (OPAC) is presented. This new OPAC features new functionalities and utilizes web 2.0 technologies in order to deliver improved search and retrieval services. Some of these new services include social tag annotations, user opinions and ranks and tag-based similarity searches. The prototype is evaluated by a user group through questionnaires, interviews and with the system's integrated logging mechanism. The results are encouraging enough an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Documents obtained using the related search function based on the Gavrilis et al, (2008) article and using all three search functions (i.e., all references, all authors, and all keywords) demonstrated this. Results yielded 710 documents that shared at least one common reference, 42 documents that shared at least one author, and 4,452,046 documents that shared at least one keyword with the target article (Gavrilis et al, 2008). The 710 documents retrieved by all references were sorted by relevance (and not by the number of common references as with Web of Science).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Documents obtained using the related search function based on the Gavrilis et al, (2008) article and using all three search functions (i.e., all references, all authors, and all keywords) demonstrated this. Results yielded 710 documents that shared at least one common reference, 42 documents that shared at least one author, and 4,452,046 documents that shared at least one keyword with the target article (Gavrilis et al, 2008). The 710 documents retrieved by all references were sorted by relevance (and not by the number of common references as with Web of Science).…”
Section: Discussionmentioning
confidence: 78%
“…This search yielded twelve documents, of which three were relevant. The most relevant of those was, "Enhancing library services with Web 2.0 functionalities" by Gavrilis, Kakali, and Papatheodorou (2008) A review of the related records for this article retrieved 371 documents with at least one reference in common. Further analysis identified four relevant documents with three references in common with the target article.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea survived into the twentieth century in the form of the catalog cards that librarians used to record a book's title, author, subject, etc. before library records were moved to computers (Gavrilis et al, 2008). The actual books constituted the data; the catalogue cards comprised the metadata.…”
Section: From Folksonomies To Fuzzy Ontologiesmentioning
confidence: 99%